Business Case: Green-Certified Buildings in South Africa’s Residential Rental Market - Roodt, Ilona (University of the Witwatersrand, Johannesburg, 2025)
In this paper, the characteristics of the Excellence in Design for Greater Efficiencies (EDGE) green building certification system is explained, and the energy and water savings in a portfolio of residential units in the EDGE-certified residential building portfolio in South Africa was investigated. This research analysed the efficiency of energy and water usage, following certification, and the contribution to lowering building running costs and increasing property values was investigated. The research revealed that the portfolio design of EDGE-certified buildings results is, on average, a 42% energy saving and a 54% water saving across the portfolio. The research explores the overall reduction in building operating costs and the impact on property return by considering the payback period of the additional investment. The US Green Building Council indicate operating costs drop by 13%, with a drop of 10.5% in the first year and then an average of 16.9% over five years. The research revealed that overall cost savings are significant, the cost of greening is recouped on average over 6 years and this means that property returns increase. The US Green Building Council indicate that property values increase by between 4%-6% for a study relating to LEED-certified buildings. The research signifies the importance of bringing down energy and water costs to preserve and increase return and value, and this may be catalytic in increasing affordable housing investment and tenant standards of living. Where this activity is at scale within the right policy framework, an overall reduction in emissions may occur.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Energy Leadership, to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: Green building certification; Energy savings; Water savings; Excellence in Design for Efficiencies “EDGE”; Sustainability; Resource saving; Reduced operating costs; Enhanced property values; Shorter payback period on investment outlay; South Africa; Energy efficiency; Affordable housing; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-7: Affordable and clean energy